2019
DOI: 10.1111/lcrp.12150
|View full text |Cite
|
Sign up to set email alerts
|

Psycholinguistic and socioemotional characteristics of young offenders: Do language abilities and gender matter?

Abstract: Purpose Previous research demonstrates an association between developmental language disorder (DLD) and criminal offending. International research also implicates alexithymia as being over‐represented in forensic samples. This study provides a comprehensive examination of the psycholinguistic and socioemotional profiles of males and females in the youth justice system, with a focus on first‐time entrants. In the context of restorative justice (RJ) underpinning youth justice disposals, this allows for informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 70 publications
1
25
0
2
Order By: Relevance
“…Findings have suggested that men are less lingually advanced than their female counterparts (Wallentin, 2020), which is said to be further exaggerated by offending status (Winstanley, Webb, & Conti-Ramsden, 2019). Apperly and Butterfill (2009), and more recently Meinhardt-Injac, Daum, Meinhardt and Persike (2018), noted that reflexive-cognitive processes (language) is required to understand the mental state of another person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings have suggested that men are less lingually advanced than their female counterparts (Wallentin, 2020), which is said to be further exaggerated by offending status (Winstanley, Webb, & Conti-Ramsden, 2019). Apperly and Butterfill (2009), and more recently Meinhardt-Injac, Daum, Meinhardt and Persike (2018), noted that reflexive-cognitive processes (language) is required to understand the mental state of another person.…”
Section: Discussionmentioning
confidence: 99%
“…Language development may offer one explanation as to why an interaction between gender and offending status, in relation to verbal ToM, was found only in the male groups. Findings have suggested that men are less lingually advanced than their female counterparts (Wallentin, 2020), which is said to be further exaggerated by offending status (Winstanley et al, 2019). Apperly and Butterfill (2009), and more recently Meinhardt-Injac et al (2018), noted that reflexive-cognitive processes (language) is required to understand the mental state of another person.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also demonstrated an association between developmental language disorder and criminal offending, even after controlling for potential confounders such as socio-economic position and years of schooling (Bryan et al 2015). Young Offenders (YO) with DLD have been found to have mean language scores of more than 2.25 standard deviations below the normative mean, and they also demonstrate greater literacy and socio-emotional difficulties than the general YO population (Winstanley et al, 2019). These communication difficulties potentially compromise a young person's ability to engage in any offender rehabilitation interventions or strategies.…”
Section: Case Management Of Children With Language Disordermentioning
confidence: 99%
“…The challenges that YOs with DLD are likely to face when participating in the YJS have been considered from various angles, with numerous studies having assessed particular linguistic or pragmatic skills in YOs that are deemed relevant to YJS interactions. These have included understanding of key legal vocabulary, such as 'caution' and 'penalty' (Sanger, Moore-Brown, Magnuson, & Svoboda, 2001), the ability to correctly interpret non-literal language (Snow & Powell, 2008 and comprehension of longer spoken passages (Gregory & Bryan, 2011;Kippin et al, 2018;Winstanley, Webb, & Conti-Ramsden, 2019). Young offenders' expressive skills have also been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%